Toward a new interior : an anthology of interior design theory - Weinthal, Lois. (New York : Princeton Architectural Press, 2011)
Interior design, as a relatively young discipline within the academic world of design, has historically been interpreted as an extension of other fine arts. Narratives exist, but they all too often treat interior design as a function of architecture or display rather than experience. An independent interior design theory is virtually nonexistent. Professor Lois Weinthal envisions a future where interior design is treated with parity to architecture and industrial design, a future with a new interior. A reader for architects and interior designers, Weinthal has carefully curated a collection of forty-eight essays that will form the foundation of interior design theory and shape future interior space. Her introductory essays illuminate each source, prefacing and directing discussion of the material as it relates to interior design theory. Alluding to Le Corbusier s classic text, she has organized this material into a framework that inspires conversation, marking a break with the past and forming a new vocabulary for the discourse. Contributions to the book s eight sections include essays by David Batchelor, Aaron Betsky, Petra Blaisse, Andrew Blauvelt, Beatriz Colomina, Le Corbusier, Robin Evans, Adolf Loos, Ellen Lupton, Charlotte Perkins Gilman, Michel Serres, Henry Urbach, Wim Wenders, and Mark Wigley.
Body and perception -- Clothing and identity -- Furniture and objects -- Color and surfaces -- Mapping the interior -- Private chambers -- Public performance -- Bridging the interior and exterior.
Includes bibliographical references and index.
Keywords: INTERIOR ARCHITECTURE -- PHILOSOPHY